HIV Suppression Restores the Lung Mucosal CD4+ T-Cell Viral Immune Response and Resolves CD8+ T-Cell Alveolitis in Patients at Risk for HIV-Associated Chronic Obstructive Pulmonary Disease. (9th September 2016) - Popescu, Iulia; Drummond, M. Bradley; Gama, Lucio; Lambert, Allison; Hoji, Aki; Coon, Tiffany; Merlo, Christian A.; Wise, Robert A.; Keruly, Jeanne; Clements, Janice E.; Kirk, Gregory D.; McDyer, John F.
Abstract : Background: Lung CD4 + T-cell depletion and dysfunction, CD8 + T-cell alveolitis, smoking, and poor control of human immunodeficiency virus (HIV) are features of HIV-associated chronic obstructive pulmonary disease (COPD), but these changes have not been evaluated in smokers at risk for COPD. We evaluated the impact of viral suppression following initiation of antiretroviral therapy (ART) on HIV-specific immunity and the balance of the CD4 + T-cell to CD8 + T-cell ratio in the lung. Methods: Using flow cytometry, we assessed the T-cell immune response in lung and blood specimens obtained from 12 actively smoking HIV-positive patients before ART initiation and after ART-associated viral suppression. Results: HIV suppression resulted in enhanced lung and systemic HIV-specific CD4 + T-cell immune responses without significant changes in CD8 + T-cell responses. We observed an increase in lung ratios of CD4 + T cells to CD8 + T cells and CD4 + T-cell frequencies, decreased CD8 + T-cell numbers, and resolution of CD8 + T-cell alveolitis after ART in 9 of 12 individuals. Viral suppression reduced Fas receptor and programmed death 1 expression in lung CD4 + T cells, correlating with enhanced effector function and reduced susceptibility to apoptosis. HIV suppression rescued peripheral but not lung HIV-specific CD4 + T-cell proliferation, resulting in augmented effector multifunction. Discussion: Together, our results demonstrate that HIV suppression restores lung mucosal HIV-specific CD4 + T-cell multifunctional immunity and balance in the ratio of CD4 + T cells to CD8 + T cells, often resolving CD8 + T-cell alveolitis in active smokers. Peripheral expansion and redistribution of CD4 + T cells and increased resistance to apoptosis are 2 mechanisms contributing to immunologic improvement following viral suppression in patients at risk for HIV-associated COPD.